The Potential of Postmortem Imaging in Heatstroke Diagnosis: A Medicolegal Study in Vietnam - Nguyen Trangh; Wang, Hui (Sriwijaya Journal of Forensic and Medicolegal, 2023)
Introduction: Heatstroke is a life-threatening medical emergency with a high mortality rate, particularly in tropical regions like Vietnam. Accurate diagnosis is crucial for both clinical management and medicolegal investigations. Postmortem imaging techniques, such as computed tomography (CT) and magnetic resonance imaging (MRI), offer a non-invasive means of assessing internal organ damage associated with heatstroke. This study aimed to evaluate the utility of postmortem imaging in diagnosing heatstroke and its associated complications in the Vietnamese population. Methods: A retrospective analysis was conducted on medicolegal autopsy cases involving suspected heatstroke deaths in Vietnam between 2018 and 2023. Postmortem CT and/or MRI scans were performed prior to autopsy, and findings were correlated with autopsy results, including histopathological examination. Results: A total of 120 cases were included in the study. Postmortem imaging revealed characteristic findings associated with heatstroke, such as cerebral edema, pulmonary edema, and multiorgan congestion. These imaging findings were consistent with autopsy and histopathological results in the majority of cases. In some instances, imaging identified subtle findings, such as early myocardial injury, that were not readily apparent at autopsy. Conclusion: Postmortem imaging, particularly CT and MRI, can play a valuable role in the diagnosis of heatstroke and its complications in medicolegal investigations. These techniques offer a non-invasive means of visualizing internal organ damage and can complement traditional autopsy findings. Further research is warranted to establish standardized imaging protocols and to explore the potential of advanced imaging techniques, such as diffusion-weighted imaging, in heatstroke diagnosis.